2019
DOI: 10.3390/cells9010051
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Role of CD11b+Ly6G−Ly6C− Myeloid-Derived Cells on the Progression of the Primary Tumor and Therapy-Associated Recurrent Brain Tumor

Abstract: Myeloid-derived cells have been implicated as playing essential roles in cancer therapy, particularly in cancer immunotherapy. Most studies have focused on either CD11b+Ly6G+Ly6C+ granulocytic or polymorphonuclear myeloid-derived suppressor cells (G-MDSCs or PMN-MDSCs) or CD11b+Ly6G−Ly6C+ monocytic MDSCs (M-MDSCs), for which clear roles have been established. On the other hand, CD11b+Ly6G−Ly6C− myeloid-derived cells (MDCs) have been less well studied. Here, the CD11b-diphtheria toxin receptor (CD11b-DTR) trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…[23] We found that these F4/80 + macrophages/microglia were critical in increasing tumor mean vessel density and promoting tumor recurrence following drug treatment. [24] However, it did not distinguish macrophages from microglia in this in vivo model, and the detailed mechanism of how microglia affect brain tumor resistance to chemotherapy is still unclear.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…[23] We found that these F4/80 + macrophages/microglia were critical in increasing tumor mean vessel density and promoting tumor recurrence following drug treatment. [24] However, it did not distinguish macrophages from microglia in this in vivo model, and the detailed mechanism of how microglia affect brain tumor resistance to chemotherapy is still unclear.…”
Section: Introductionmentioning
confidence: 78%
“…Cell lines culture Murine astrocytoma cell line, ALTS1C1 (T8239, Applied Biological Materials, Richmond, Canada, or BCRC60582, Hsinchu, Taiwan), and a stable clone of ALTS1C1-Tk was previously established in our lab. [23,24] ALTS1C1-GFP cell line was created by lentiviral infection of GFP-expressing vector into the ALTS1C1 cells, ALTS1C1-GFP-Tk cell line was created by transfection of herpes simplex virus thymidine kinase (HSV-Tk) gene into the ATLS1C1-GFP cell line. UN-KC-6141, a pancreatic adenocarcinoma cell line, was kindly provided by Prof. Surinder K. Batra at the University of Nebraska Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…Myeloid-derived cells have been indicated as an essential factor in the immune system, particularly in cancer immunotherapy. Two subtypes of MDSCs have clear roles that have been established in murine: CD11b + Ly6G-Ly6C + monocytic MDSCs (M-MDSCs) and CD11b + Ly6G + Ly6C- polymorphonuclear or granulocytic myeloid-derived suppressor cells (PMN-MDSCs or G-MDSCs) ( Wu and Chiang, 2019 ). Generally, PMN-MDSCs make up the majority of the population of MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The former express have the cell surface marker phenotype CD11b + Ly6ClowLy6G + , while the latter are characterized by a CD11b + Ly6ChighLy6Gphenotype. 164,165 Human MDSCs are different from murine MDSCs, which are characterized by no or low expression of HLA-DR and high expression of CD33. Unsurprisingly, the common myeloid biomarker CD11b is also a marker of human MDSCs, and the CD11b and CD33 double-positive HLA-DR-low population can be further classified as M or G MDSCs according to their CD14 or CD15 expression.…”
Section: The Immune Microenvironment Of Osteosarcomamentioning
confidence: 99%